2012
DOI: 10.6004/jnccn.2012.0075
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine Tumors

Abstract: Neuroendocrine tumors comprise a broad family of tumors, the most common of which are carcinoid and pancreatic neuroendocrine tumors. The NCCN Neuroendocrine Tumors Guidelines discuss the diagnosis and management of both sporadic and hereditary neuroendocrine tumors. Most of the recommendations pertain to well-differentiated, low- to intermediate-grade tumors. This updated version of the NCCN Guidelines includes a new section on pathology for diagnosis and reporting and revised recommendations for the surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
127
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 170 publications
(134 citation statements)
references
References 132 publications
0
127
3
1
Order By: Relevance
“…For these patients, standard dosing may not be sufficient to obtain symptom control; therefore, an above-standard dose of SSA may be considered as an attempt to control CS symptoms associated with NET. Additional recommendations (e.g.,National Comprehensive Cancer Network) and consensus reports have recommended considering an increase of dosage or dose frequency of octreotide LAR for refractory CS symptoms [18][19][20].…”
Section: (85)mentioning
confidence: 99%
“…For these patients, standard dosing may not be sufficient to obtain symptom control; therefore, an above-standard dose of SSA may be considered as an attempt to control CS symptoms associated with NET. Additional recommendations (e.g.,National Comprehensive Cancer Network) and consensus reports have recommended considering an increase of dosage or dose frequency of octreotide LAR for refractory CS symptoms [18][19][20].…”
Section: (85)mentioning
confidence: 99%
“…Incluyen una amplia familia de tumores, de los cuales los más frecuentes son los carcinoides y los tumores neuroendocrinos del páncreas (TNEP) 2 . Los TNEP representan aproximadamente el 2% de los tumores gastrointestinales y el 1-2% de los tumores pancreáticos 3 .…”
Section: Introductionunclassified
“…According to the National Comprehensive Cancer Network guidelines and American Joint Committee on Cancer staging of gastrointestinal NETs (14), T1 tumors that are limited to the lamina propria or submucosa and present a diameter of <1 cm (the diameter of colorectal and appendix ≤2 cm), are considered appropriate for endoscopic resection (15,16). However, previous studies have reported that patients with such tumors have experienced lymphatic-vascular involvement and exhibit the risk of recurrence and metastasis following endoscopic resection (13).…”
Section: Introductionmentioning
confidence: 99%